Detailed Soluble Proteome Analyses of a Dairy-Isolated Enterococcus faecalis: A Possible Approach to Assess Food Safety and Potential Probiotic Value - Cirrincione, Simona; Neumann, Bernd; Zühlke, Daniela; Riedel, Katharina; Pessione, Enrica (Frontiers in Nutrition, 2019)
Enterococci are common inhabitants of the gastrointestinal tracts of humans and animals and thanks to their capability to tolerate different environmental conditions and their high rates of gene transfer, they are able to colonize various ecological niches, as food matrices. Enterococcus faecalis bacteria are defined as “border line” microorganisms. From one side they are used as food starters, bio-control agents and probiotics to improve human or animal health. From the other side, in the last two decades enterococci have emerged as important nosocomial pathogens, because bearing high-level of resistance to antibiotics and several putative virulence factors. In this study, the proteomic (LC-MS/MS) and the phenotypic characterization (enzymatic methods) of three strains of E. faecalis with different origin were performed in order to investigate the differences and/or similarities occurring between pathogenic and health promoting bacteria. The E. faecalis D27 isolated as cheese contaminant, E. faecalis Symbioflor 1 a probiotic strain and E. faecalis UW3114 a clinical isolate involved in urinary tract infection were the objects of the study. The comparison of cytosolic protein expression profiles of the three strains, highlighted statistically significant changes in the abundance of proteins mainly involved in specific metabolic pathways, nutrient transport, stress response and cell wall modulation. Moreover, especially in the food contaminant and the clinical isolate, several proteins with potential pathogenic implications were found. The analysis of the extracellular proteome provided interesting results concerning proteins involved in bacterial communication, such as pheromones and conjugative elements and also proteins able to interact with human components. The phenotypic assays evaluating i) biofilm formation ii) hemolytic activity on blood agar plates iii) protease activity, allowed typing of bacteria in relation to well-known pathogenic traits. The obtained results confirmed the pathogenic profile associated to the clinical isolate as compared to the food contaminant and to the probiotic and allowed to elucidate the risks associated with the poor characterized foodborne E. faecalis D27.